Effectiveness of the Application of Range of Motion (ROM) with the Cylindrical Grip Method on Increasing Upper Extremity Muscle Strength in Non-Hemorrhagic Stroke Patients: A Systematic Review - Khairatun Hisan, Wildani; Abdul Muhith (Journal of Applied Nursing and Health, 2024)
Background: The Ministry of Health revealed that in 2023, stroke cases will increase, and funding for stroke will be very large, causing other diseases. Therefore, patients must carry out the cylindrical grip method independently without large costs. ] This study aims to assess the effectiveness of applying Range of Motion (ROM) exercises using the Cylindrical Grip method to enhance upper extremity muscle strength in non-hemorrhagic stroke patients. Methods: A literature review was carried out using PRISMA flow diagrams. The journal databases used are Google Scholar and Scopus. Inclusion criteria include articles that focus on the effect of the cylindrical grip method on non-hemorrhagic stroke patients, journals for the last 5 years, full pdf access, the exclusion criteria are research articles of the review type. Results: The search results obtained 10 journals by searching two databases: Google Scholar and Scopus Conclusion: The cylindrical grip method significantly increases muscle strength in non- hemorrhagic stroke patients and can be used as a gradual mobilization method that can be carried out at home independently by the patient.